Leveraging AI for Advanced Troubleshooting in Telecommunications: Enhancing Network Reliability, Customer Satisfaction, and Social Equity - Singh, Puneet (Journal of Science & Technology, 2021)
The integration of Artificial Intelligence (AI) in telecommunications is poised to revolutionize the industry's approach to troubleshooting, offering a transformative solution to the persistent challenges of network reliability, customer satisfaction, and social equity. This paper delves into the application of AI-driven methodologies in proactively predicting, identifying, and resolving network issues, thereby significantly enhancing the performance and dependability of telecommunication networks. The research begins with a thorough examination of the current landscape in telecommunications, highlighting the technical and operational challenges associated with traditional troubleshooting methods, which are often reactive, time-consuming, and prone to human error. These conventional approaches are increasingly inadequate in addressing the complexities of modern, large-scale networks, where the rapid proliferation of connected devices and the demand for uninterrupted services necessitate more sophisticated and efficient solutions.AI, with its ability to process vast amounts of data in real time, offers a paradigm shift in troubleshooting by enabling predictive maintenance, anomaly detection, and automated resolution processes. This paper explores the various AI techniques, including machine learning algorithms, deep learning models, and natural language processing, that are being integrated into telecom networks to facilitate advanced troubleshooting. By analyzing historical data, identifying patterns, and learning from past incidents, AI systems can preemptively address potential network failures before they impact users, thus reducing downtime and ensuring a more resilient network infrastructure. The research also addresses the technical challenges of implementing AI in telecommunications, such as the integration of AI with existing network management systems, the scalability of AI solutions in large networks, and the need for continuous learning and adaptation of AI models to cope with evolving network dynamics.The paper provides a detailed analysis of case studies where AI-driven troubleshooting has been successfully implemented in real-world telecom scenarios. These case studies demonstrate the practical benefits of AI, including significant reductions in mean time to repair (MTTR), cost savings through optimized resource allocation, and enhanced customer satisfaction due to fewer service disruptions and faster issue resolution. Moreover, the paper emphasizes the social implications of leveraging AI in telecommunications, particularly in promoting social equity. Improved network reliability and performance, driven by AI, can enhance access to critical communication services in underserved and rural communities, bridging the digital divide and fostering greater inclusion in the digital economy. The research highlights how AI can enable telecom providers to offer more equitable services, ensuring that all segments of society benefit from reliable and high-quality telecommunications.This paper asserts that the integration of AI into telecommunications is not only a technical necessity for improving network reliability and customer satisfaction but also a crucial step toward achieving broader social equity in access to communication technologies. The findings underscore the potential of AI to transform the telecommunications industry by enabling proactive and efficient troubleshooting, ultimately leading to a more resilient, customer-centric, and socially responsible telecom infrastructure. The research contributes to the ongoing discourse on the future of telecommunications by providing insights into the practical applications of AI, the challenges that need to be addressed, and the potential social benefits that can be realized through the widespread adoption of AI-driven solutions in the industry.
Keywords: Telecommunications; Social Equity .; Artificial Intelligence; troubleshooting; network reliability; customer satisfaction; social equity; Predictive Maintenance